An Indium‐Free Low Work Function Window Electrode for Organic Photovoltaics Which Improves with In‐Situ Oxidation. (26th October 2012) - Hutter, Oliver S.; Stec, Helena M.; Hatton, Ross A.
<x xml:space="preserve">Abstract</x> A low‐cost window electrode for organic photovoltaics that simultaneously removes the requirement for conducting oxide and conventional low work function electrodes and functions as a sink for oxygen/water in the heart of the device. Remarkably the functionality of this electrode, which is based on a 7.8 nm nanostructured Cu:Al film, improves upon in situ oxidation as demonstrated in bulk heterojunction organic photovoltaics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>